Interactions between elevated CO2 levels and floating aquatic plants on the alteration of bacterial function in carbon assimilation and decomposition in eutrophic waters. (15th March 2020) - Shi, Man; Li, Jiangye; Zhou, Qi; Wang, Guibin; Zhang, Weiguo; Zhang, Zhenhua; Gao, Yan; Yan, Shaohua
Abstract: Elevated atmospheric CO2 concentration (eCO2 ) may have different effects on the bacterial community with regard to C assimilation and decomposition in eutrophic waters compared to that in fresh waters with intermediate levels of nutrients and oceans. Aquatic plant growth under eCO2 could further modify microbial activities associated with the C cycle in eutrophic waters. Therefore, there is an urgent need to further study how eCO2 and its interactions with the growth of aquatic plants affect the composition and function of the bacterial community involved in mediating the C cycle in eutrophic waters. Accordingly, we designed a microcosm experiment to investigate the effects of ambient and high CO2 concentrations on bacterial community composition and function in eutrophic waters with and without the growth of Eichhornia crassipes (Mart.) Solms. The results from 16S rRNA gene sequencing, function prediction, and q-PCR showed that eCO2 significantly increased the abundance of bacterial and functional genes involved in CO2 assimilation (photosynthetic bacteria; cbbL IA & IC, cbbL ID, cbbM, pufM ) and C decomposition (Acidimicrobiia, Thermoleophilia, Gaiellales; ChiA ), illustrating the functional enrichment with photoautotrophy, hydrocarbon degradation, cellulolysis, and aromatic hydrocarbon degradation. However, eCO2 decreased the abundance of some chemoautotrophic bacteria, including nitrifying bacteria (Nitrospirae, Nitrosomonadaceae ). In contrast, the cultivation of E. crassipes decreased the abundance of photosynthetic bacteria but increased the abundance of bacteria involved in complex C decomposition associated with root exudates and degradation, e.g. Fibrobacteres, Sphingobacteriales, Sphingomonadales, and Rhizobiales. eCO2 and growth of E. crassipes had opposite effects on algal density in eutrophic waters, creating interactive effects that further decreased the diversity of the bacterial community and abundance of some CO2 -assimilating bacteria with nitrifying characteristics ( Nitrosomonadaceae ) and some C-degrading bacteria (Fibrobacteres) with denitrifying properties ( Flavobacteriaceae, Sphingomonadaceae, and Gemmobacter ). Therefore, the interactions between aquatic plants and the bacterial community in eutrophic waters under eCO2 would be beneficial to the environment and help alleviate the greenhouse effect. Graphical abstract: Image 1 Highlights: The eCO2 and plant growth had opposite impact on the CO2 -assimilating bacteria. The eCO2 and aquatic plant growth increased the abundance of C-degrading bacteria. Interactions of eCO2 and plant decreased CO2 -assimilating and C-degrading bacteria. Growing aquatic plants under eCO2 would be benefit for alleviating greenhouse effect.